Detection of TPO antibody and TFT among Thyroiditis patients in Thi-Qar Governorate, Iraq - gaseb, Noor; Hamim, Saad; A. Almankhee, Ahmed (University of Thi-Qar Journal of Science, 2024)
Thyroiditis is a general term that refers to thyroid gland inflammation. The present research was conducted to identify the role of thyroid peroxidase antibodies (TPO-Ab) in Thyroiditis patients and assaying the levels of thyroid function tests (TFT), which include levels of serum triiodothyronine hormone (T3), thyroxin hormone (T4), and thyroid stimulating hormone (TSH). A total of 86 serum samples (76 thyroiditis patients and 10 controls) from August 2023 to November 2023, at Al-Haboby Teaching Hospital and some private clinics in Thi-Qar Governorate were enrolled in the present study. The sandwich-ELISA technique assayed the levels of TPO-Ab, and the levels of (TFT) T3,T4, and TSH by using a competitive binding assay. Thyroiditis patients were divided into hypothyroidism and hyperthyroidism type with 47(61.84%) and 29(38.16%) patients, respectively (P≤0.05). Hypothyroidism and hyperthyroidism groups showed elevated mean serum levels of TPO-Ab (29.78%) and (20.68%) for members of each group separately, with a mean of (478.8) and (1070), respectively. While the mean of TPO-Ab in the control group was (319.5). The means of TFT in hypothyroidism group for T3,T4 and TSH were (0.9215), (5.402), and (22.86), respectively. The means of TFT in hyperthyroidism group for T3,T4 and TSH were (1.003), (7.409) and (0.3893), respectively, compared to the control. The mean of TFT for T3,T4 and TSH was (0.781), (7.374), and (1.603), respectively.